O PROCESSO DE ESCOLHA DO LIVRO DIDÁTICO DE LÍNGUA PORTUGUESA DAS SÉRIES FINAIS DO ENSINO FUNDAMENTAL - Oliveira, Luciano de (2011)
This research discusses the public policy of the textbook, obtained by following the guidelines of the Programa Nacional do Livro Didático (PNLD). Study focuses on the process of choosing textbook of Language Portuguese, the final fundamental teaching education in state education. Its main objective is to understand how it happens inside of school, the process of choosing textbook and how teachers use the textbook in their teaching. To collect this information, interviews were conducted with pedagogues and teachers of Language Portuguese who worked in state schools in the city of Ponta Grossa - PR. These interviews were recorded and transcribed after read several times, with the aim of identifying the key points of information to list, the very speech of the subjects studied, categories of analysis. After identifying these categories, the individual speeches were organized into collective discourses. This procedure of organizing the data collected was inspired by the DSC (Collective Subject Discourse) and Lefevre and Lefevre (2005). For the discussion of data, Oliveira and Guimarães (1984), Freitag et. al (1987, 1993), Baptist (2001, 2004), Cury (2009) helped to rescue historical and political aspects of the textbook. The authors Apple (1995), Heller (1989) and Chartier (2002) helped to expand the concepts of the textbook, on the routine of school and to the understanding of the them practices in the classroom, using the textbook. The result of analises showed that there is some mismatch between what it proclaims the official documents on how it should happen to choose the textbooks and the practices that are effective within the school. Another point highlighted was that the printed material, the textbook, provided by MEC, chosen by teachers, is in an important support material for teachers, however its use in the classroom is not appropriate in light of obstacles bureaucratic policy itself (PNLD). It was verified that the Brazilian state catalyzed since the beginning of the 1st law of textbooks, intellectuals and groups in a certain social recognition and academic, was mixed ideological to compose the team of MEC, set policy, to classify the books available for analysis at the federal level, in order to ensure the legitimacy of state action. The study showed that the product textbook has played and continues to play a decisive role in political clashes between the established state and civil society as it meets the interests of economic, social, political and religious groups in certain editorials.